THE LEXICON OF CONTEMPORARY WAR TIME: COMPRESSIVE PROFESSIONAL SLANG UNITS IN THE UKRAINIAN LANGUAGE - Oleksandr S. Ivko; Natalia V. Diachok (Alfred Nobel University Journal of Philology, 2024)
The article seeks to reveal the concept of compressive processes implemented in the professional slang of Ukrainian military people and volunteers. It is a conti nuati on of a series of works covering the cur- of Ukrainian military people and volunteers. It is a conti nuati on of a series of works covering the cur- of Ukrainian military people and volunteers. It is a conti nuati on of a series of works covering the cur- Ukrainian military people and volunteers. It is a conti nuati on of a series of works covering the cur- Ukrainian military people and volunteers. It is a conti nuati on of a series of works covering the cur- military people and volunteers. It is a conti nuati on of a series of works covering the cur- military people and volunteers. It is a conti nuati on of a series of works covering the cur- people and volunteers. It is a conti nuati on of a series of works covering the cur- people and volunteers. It is a conti nuati on of a series of works covering the cur- and volunteers. It is a conti nuati on of a series of works covering the cur- and volunteers. It is a conti nuati on of a series of works covering the cur- volunteers. It is a conti nuati on of a series of works covering the cur- volunteers. It is a continuation of a series of works covering the cur- rent processes in language and speech. The main focus here is placed on abbreviation and univerbation as the processes able to create compressed modification of nominative units – both analytical, and synthetic, i.e., the processes belonging to internal, speech-based word formation. The topicality of the paper lies in its focus on phenomena that gradually become the history of the Ukrainian language and Slavic studies as a whole, including neologization and adjacent phenomena. Тhe research aims to define the productivity of compressives as units of military discourse, on one hand, and as the emergent linguistic material, on the other. The objectives of the study are as follows: 1) to separate compressives from the traditional derivates; 2) to determine the criteria for distinguishing the main compressive processes – abbreviation and univerbation; 3) to formulate the causes of the emergence of the investigated slang; 4) to give reasoning for the study of compressives in military discourse as a pro- spective research issue. The main research methods include the descriptive and structural ones, as they help demonstrate the specificity of univerbs and abbreviation as instances of speech compression. We have utilized the dis- tributive analysis approach to determine the types of nominative units’ transformation. Military discourse is the field of language functioning that fosters the production of neologisms emerging as a result of different types of compression. It reflects the dynamic nature of military discourse with its need to convey maximum amount of information within the minimum period of time, striving for clearance, laconic forms, and rich content. Within the range of Ukrainian military lexicon under analysis, we single out nouns (formed by means of abbreviation, univerbation, and simulation of univerbation) as well as verbs and their verb forms (which often result from univerbation). The emergence of compressive nominations in question follows the general tendency of lexical nomination towards modifying analytical or complex synthetic units into shorter speech segments, being a universal feature of the current state of the Indo-European languages as a whole.